Bioequivalence of generic alendronate sodium tablets (70 mg) to Fosamax® tablets (70 mg) in fasting, healthy volunteers: a randomized, open-label, three-way, reference-replicated crossover study - Zhang Y; Chen X; Tang Y; Lu Y; Guo L; Zhong D (Dove Medical Press, 2017)
Yifan Zhang,1 Xiaoyan Chen,1 Yunbiao Tang,2 Youming Lu,1 Lixia Guo,1 Dafang Zhong1 1State Key Laboratory of Drug Research, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, 2Department of Pharmacy, The General Hospital of Shenyang Military Region, Shenyang, People’s Republic of China Purpose: The aim of this study was to evaluate the bioequivalence of a generic product 70 mg alendronate sodium tablets with the reference product Fosamax® 70 mg tablet. Materials and methods: A single-center, open-label, randomized, three-period, three-sequence, reference-replicated crossover study was performed in 36 healthy Chinese male volunteers under fasting conditions. In each study period, the volunteers received a single oral dose of the generic or reference product (70 mg). Blood samples were collected at pre-dose and up to 8 h after administration. The bioequivalence of the generic product to the reference product was assessed using the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) reference-scaled average bioequivalence (RSABE) methods. Results: The average maximum concentrations (Cmax) of alendronic acid were 64.78±43.76, 56.62±31.95, and 60.15±37.12 ng/mL after the single dose of the generic product and the first and second doses of the reference product, respectively. The areas under the plasma concentration–time curves from time 0 to the last timepoint (AUC0–t) were 150.36±82.90, 148.15±85.97, and 167.11±110.87 h·ng/mL, respectively. Reference scaling was used because the within-subject standard deviations of the reference product (sWR) for Cmax and AUC0–t were all higher than the cutoff value of 0.294. The 95% upper confidence bounds were -0.16 and -0.17 for Cmax and AUC0–t, respectively, and the point estimates for the generic/reference product ratio were 1.08 and 1.00, which satisfied the RSABE acceptance criteria of the FDA. The 90% CIs for Cmax and AUC0–t were 90.35%–129.04% and 85.31%–117.15%, respectively, which were within the limits of the EMA for the bioequivalence of 69.84%–143.19% and 80.00%–125.00%. Conclusion: The generic product was bioequivalent to the reference product in terms of the rate and extent of alendronate absorption after a single 70 mg oral dose under fasting conditions. Keywords: alendronate sodium, pharmacokinetics, highly variable drug, reference-scaled average bioequivalence